Linguistic Realization of Legitimation of Power by Zia ul Haq and Pervez Musharraf during the Afghanistan Wars - Waqasia Naeem; Dr. Muhammad Shaban Rafi (Journal of Political Studies, 2019)
This research aims at revealing the linguistic realization of legitimation in the discourses of Zia and Musharraf during the Afghanistan wars for the periods of 1979- 1988 and 2001-2008. The data comprises of their official discourses on Afghanistan war during their respective regimes as head of the state. Using the Nomination strategies suggested by Discourse Historical Approach by Wodak and Meyer (2001) and Van Leeuwen‟s Social Actors Representation model (2008), this study reveals the linguistic realization of legitimation through the dichotomous construction of self and Other representation. Moreover, it is argued in the study that different social actors have been constructed in their discourses through the categorization of Inclusion/Exclusion and Activation/Passivation to rationalize the perspective of self/ in-group, in order to justify their respective policies on Afghanistan issue.